'Falsehood flies, and the truth comes limping after it': social media and public health. Issue 5 (September 2021) - Moore, Justin B.; Harris, Jenine K.; Hutti, Ellen T.
Abstract : Purpose of review: To highlight the various uses of social media by public health practitioners and organizations, with special emphasis on how social media has been successfully applied and where applications have struggled to achieve the desired effects. Recent findings: Social media has been used effectively in improving the timeliness and accuracy of public health surveillance. Social media has also been used to communicate information between public health organizations and reinforce consistent messaging about enduring threats to public health. It has been applied with some success to coordinate of disaster response and for keeping the public informed during other emergency situations. However, social media has also been weaponized against the public health community to spread disinformation and misinformation, and the public health community has yet to devise a successful strategy to mitigate this destructive use of social media. Summary: Social media can be an effective tool for public health practitioners and organizations who seek to disseminate information on a daily basis, rapidly convey information in emergent situations, and battle misinformation. Social media has been uniquely valuable and distinctly destructive when it comes to protecting and improving public health.